Innovation of the EDDIS-balita mobile application: An educational and early detection solution for stunting in toddlers to enhance early prevention - Sri Mulyanti; Heri Maulana; Nina Pamela Sari; Asep Setiawan (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2026)
Background: Stunting is a chronic nutritional problem caused by inadequate nutrient intake and recurrent infections, particularly during the First 1,000 Days of Life (HPK). Low parental knowledge regarding balanced nutrition, sanitation, and child growth monitoring contributes to the high incidence of stunting. The use of technology, especially Android-based mobile applications widely utilized by the Indonesian population, offers a significant opportunity as an effective medium for education and early detection of stunting. Objective: To design an Android application, “EDDIS-Balita” (Early Detection and Education of Stunting in Toddlers), capable of providing accurate, practical, and easily accessible education and early detection of stunting for the wider community. Methods: This study employed the Research and Development (R&D) method with a qualitative approach. System development was conducted using the FAST (Framework for Application of Systems Technology) method, including problem identification, needs analysis, system design, and application construction using MIT App Inventor. The application features include stunting educational materials, stunting screening, stunting status calculation, and a hotline menu. Application testing was carried out using black box testing to assess the accuracy of input and output results. Results: The EDDIS-Balita application was proven to function optimally, with a 100% success rate in all tested features. All educational, screening, and calculation menus operated smoothly and were easy to use by mothers of toddlers, posyandu cadres, and healthcare workers as learning media and early detection tools. Conclusion: EDDIS-Balita is an effective innovation for enhancing community understanding of stunting prevention while facilitating independent and rapid early detection. This application has strong potential to support accelerated stunting reduction through more timely education and intervention. The study recommends further training and socialization for cadres, healthcare workers, and the community to ensure optimal utilization of the application.